Teologi Wabah Perspektif Ibnu Hajar Al-‘Asqalani dan Slavoj Ẑiẑek - Harjuna, Muhamad (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
This article discussed about the theology of pandemic in the perspective of Ibn Hajar al-'Asqalani and Slavoj Ẑiẑek. The author examined the book Badzlul Ma'ûn fi Fadhli ath-Thā'ûn and the book Pandemic, Covid-19 Shakes the World. This paper is a literature study, namely analyzing text as a source of data in the writing process. The pandemic in Ibn Hajar's perspective based on the hadith is a form of